Understanding post-career adjustment in ex-professional ice hockey enforcers: Mental health - Michael Gaetz (Taylor & Francis Group, 2022)
The focus of the manuscript is on unique stressors and mental health challenges faced by professional ice hockey enforcers during their careers and how these stressors, when combined with a history of neurotrauma, may affect functioning post-career. It was hypothesised that participants would have several challenges with mental health caused by repetitive exposure to concussive and sub-concussive events consistent with Chronic Traumatic Encephalopathy (CTE) symptomology. Ten retired professional ice hockey enforcers were interviewed to identify whether they experienced stressors or mental health challenges post-career. A mixed methods approach was utilised to develop descriptive and emergent themes and their frequencies. Participants reported a number of stressors unique to the enforcer role. Their response to these stressors was mediated by whether they embraced or tolerated/accepted the enforcer role. Two participants reported being diagnosed with depression with another stating that he had felt periods of sadness in the past. This pattern of results did not support the hypothesis. While there is some evidence to suggest that ex-professional hockey enforcers have challenges with mental health post-career, the prevalence is consistent with the estimates in the general population and with other elite athletes in other sports.